2017
DOI: 10.1038/s41598-017-11027-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Spatial Distribution and Characteristics of Lineaments Using Fractal and Multifractal Models: A Case Study from Northeastern Yunnan Province, China

Abstract: This study describes the fractal dimensions of the spatial distributions of lineaments as an index of the complexity of faults, and the results could provide new insights into the migration of ore-bearing fluid. The Segment Tracing Algorithm method is employed to extract the lineaments in northeast Yunnan Province from a remote sensing image. Box-counting fractal and multifractal models are used to analyze the fractal and multifractal spatial distribution characteristics of the linear structures. The different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Unlike D(q) and α(q), the fractal spectrum (f (α)) is a convex function of an approximate parabola [81], and its symmetry is generally expressed as shown in Equation (15). Previous studies have shown that a grid number with large probability is larger than a grid number with small probability when f (α) is a left-hook curve [3]. By contrast, a grid with a small probability has a higher number when f (α) is a right-hook curve [82].…”
Section: Multifractal Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike D(q) and α(q), the fractal spectrum (f (α)) is a convex function of an approximate parabola [81], and its symmetry is generally expressed as shown in Equation (15). Previous studies have shown that a grid number with large probability is larger than a grid number with small probability when f (α) is a left-hook curve [3]. By contrast, a grid with a small probability has a higher number when f (α) is a right-hook curve [82].…”
Section: Multifractal Characteristicsmentioning
confidence: 99%
“…Geological lineaments are defined as the straight linear elements visible at the Earth's surface, such as bedrock faults and joints, stratification, linear sand dunes, and drumlins [1], and they can be a brighter or darker line or structure than background pixels on remote sensing images, representing some geological or geomorphological phenomena, such as a trace of intersection between a planar or sub-planar structural inhomogeneity [2]. The existence of lineaments has been proven to be closely related to unexposed faults [3], reflecting patterns and anomalies (e.g., alteration) in the crust and the favorable zone for mineral deposits and processes [4,5], and controlling the position of deposit and the migration and accumulation of minerals (e.g., [4,[6][7][8][9][10]). In an active fault system, lineaments are indicative for locating the faults and determining the general structural parameters [11], and they can indirectly reflect the spatial distribution of groundwater [12], hydrothermal alteration zones [13,14], and geo-hazards [15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations